A construção social do mercado de acácia-negra no estado do Rio Grande do Sul - Lisboa, Rodrigo da Silva (2013)
For a long time the markets were seen as an abstract entity, regulated by offer and demand for products, and disconsidered the importance of social interaction in their formation. Therefore, this study aimed to comprehend the factors that contributed to and conditioned the shape of the market structure of Acacia mearnsii De Wild in Rio Grande do Sul, as well as understand the different roles of agents and institutions in the social construction of this market. This work specifically intended: identify agents that compose the market for Acacia mearnsii and their roles; map the network of relationships of the agents in the market; understand the effect of social, technical, economic and political aspects in the development of market of Acacia mearnsii in Rio Grande do Sul. For this was selected the New Economic Sociology (NES) as the theoretical basis. Pierre Bordieu was the main visited author, due of his theory of fields and capital, and for understand that the action of agents is conditioned by the existent structure and the structure is conditioned by the habitus of agents. Other authors such as Fligstein, Swedberg, Steiner and Abramovay also have meaningful participation in the study due to their contributions to the area. The methodology used to conduct this study was the case study, and the market of Acacia mearnsii was considered the case to be analyzed. To obtain the data, semi-structured interviews were realized in ten cities of RS, with the main companies of the sector, along forest producers that operate in different ways and with different strategies, and with the company Technical Assistance and Rural Extension (TARE). As a secondary source, we used data of IBGE, Emater / Ascar and various agencies connected with the section. Thus, it was concluded that the market of Acacia mearnsii is a social construct composed of several agents, identified eleven kinds, each with distinct characteristics and strategies. It was noticed that this market had its beginning promoted by the exploration of the shell for the production of tannin. In a second moment, comes the production of charcoal, the main way to use the wood until the 1990s, and from 1995 began the exploration of wood for the purpose of producing splinter for export, considerably modifying the field. It was also noticed that this market was conditioned by several factors such as the concentration of capital from major companies; the influence of formal and informal institutional environment on the action of the agents, materialized by environmental and labor laws and culture; the lack of labor, indifferently of the size of the producer; the problem of the succession of family foresters; the lack of cooperation between small producers to market their products; the ability of social enterprises and their influence on other agents; habitus colonist forester and coal producer, among others.